2021
DOI: 10.1155/2021/5341523
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Optimization Method of Visual Effect of Outdoor Interactive Advertising Assisted by New Media Technology and Big Data Analysis

Abstract: Along with the development and promotion of Internet technology, new media are increasingly diversified, enriching and changing our lives. This paper focuses on outdoor interactive advertising as a communication method, analyzing its creative features and applications. Unlike traditional advertising, where audiences receive passively, new media interactive advertising establishes a more direct communication method for consumers and products, creating different sensory stimulation and emotional experience envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Based on the hypothesis that the more hours an employee is being trained the higher the performance score, the relationship of the employee training hours to performance outcomes was modeled using Linear Regression [14]. According to regression analysis, there was a positive correlation, a dependent variable and an independent variable (R-squared = 0.75).…”
Section: Linear Regressionmentioning
confidence: 99%
“…Based on the hypothesis that the more hours an employee is being trained the higher the performance score, the relationship of the employee training hours to performance outcomes was modeled using Linear Regression [14]. According to regression analysis, there was a positive correlation, a dependent variable and an independent variable (R-squared = 0.75).…”
Section: Linear Regressionmentioning
confidence: 99%
“…Vangelov (2022) analysed digital outdoor advertising in Shanghai metro station, which promotes Nescafe products through an interactive, engaging and immersive experiencea game on a digital screen. Gan and Tsai (2021) stressed that using new technologies in outdoor advertising makes it possible to interact with consumers' sensory systems, such as vision, hearing, smell, taste, and touch. Wei et al (2021) mentioned that consumers might be exposed to outdoor advertising in many technologically innovative ways, and their purchasing behaviour or decision-making may be unintentionally influenced by such exposure.…”
Section: Entrepreneurship and Sustainability Issuesmentioning
confidence: 99%
“…Literature [13] believes that visual communication design is essentially an interactive experience of sensory stimulation and emotion, and designers can enhance the audience's attention and aesthetic vision by constructing the consumer's visual, auditory, olfactory, gustatory, and tactile sensory interaction system. Literature [14] considers aesthetic elements as a kind of visual sign, and their study of architectural design in the Dutch East Indies found that aesthetic visual signs have a certain potential and hierarchical structure, which collectively contribute to the diversity of aesthetic elements of local public architectural design in the process of dynamic development of the place.…”
Section: Introductionmentioning
confidence: 99%